Umowa o pomocy przy zbiorach — nowa podstawa prawna zatrudnienia - Florczak, Izabela (Wydawnictwo Uniwersytetu Wrocławskiego, 2019)
The labour market policy that has been developed in previous years seems to promote employment based on the labour law relationship over civil law employment. The exact opposite direction is set out by the introduction of the harvest help contract. The rationality of its introduction into the legal system is explained by economic reasons — the need to help farmers with jobs which are characterized by increased seasonal intensity. Therefore, it is important to discuss the scope of its application both in terms of subject and object matter and the conditions under which farmers’ helpers should provide their work. Their differentiation of the working conditions in comparison to other employed persons should be rationally justified by axiological reasons.
Keywords: harvest help contract; farmer’s assistant; disintegration of labour protection; civil law employment